Problem-based learning model with zoom breakout rooms application: Its impact on students' scientific literacy - Priadi, Median Agus; Marpaung, Rini Rita T.; Fatmawati, Yosy (CV FOUNDAE, 2021)
This study aims to determine whether there is an effect of the PBL model assisted by the Zoom Breakout Rooms application on the scientific literacy abilities of the students in Grade X SMA Qur'an Darul Fattah Bandar Lampung on environmental change material. The design used in this study was a quasi-experimental design with a Pretest-Postest Non-equivalent (The Non-equivalent Control Group Design). The population of this study was all students of class X SMA Qur'an Darul Fattah Bandar Lampung for the academic year 2020/2021 with a sample of 24 students selected using cluster random sampling technique, namely class X IPA A and X IPA B. The instrument used in this study is test and questionnaires. The data in this study are quantitative data obtained from the average pretest, posttest, and N-gain scores which are then analyzed statistically using an independent sample t-test at a significance level of 5% through the SPSS 26.0. The results showed the average N-gain class (55,71 ± 22,51) in the medium category and the control class (19,50 ± 16,90) in the low category. Then, the questionnaire data on student responses to Zoom Breakout Rooms and the learning implementation observation sheet were analyzed descriptively. The results showed that there was an effect of the PBL model assisted by Zoom Breakout Rooms on students' scientific literacy skills on environmental change material.